Can Rotational Grouping Be Determined by the Initial Conditions?. (January 2018) - Dobbins, Allan C.; Grossmann, Jon K.
Objects rotating in depth with an ambiguous rotation direction frequently appear to rotate together. Corotation is especially strong when the objects are interpretable as having a shared axis. We manipulated the initial conditions of the experiment by having pairs of objects initially appear to be unambiguous, and then make either a sudden or gradual transition to ambiguous spin. We find that in neither case do coaxial counter-rotating objects persist in being perceived as counter-rotating. This implies that the perceptual constraint that favors coaxial corotation overrides the initial perceptual state of the objects.